Augmented model based double iterative loop techniques for integrated system optimisation and parameter estimation of large scale industrial processes - Normah Abdullah,; Brdys, M.A.; Roberts, P.D. (1993)
Two novel hierarchical structures are presented which extend the applicability of previous model based double iterative loop techniques to non-convex problems. The methods incorporate integrated system optimisation and parameter estimation which utilizes process measurements to achieve real process optimality inspite of model reality differences. The double iterative loop structures of the proposed algorithms use the real process measurement within the outer loops while the inner loops involve model based computation only. This means that the algorithms use available information from the real process efficiently and a significant reduction in set-point alterations to real subprocesses is achieved. In order to cater for process complexity the inner loops are organised in the form of two level hierarchical structures. The paper presents the convergence conditions of the augmented techniques and simulation examples are provided to illustrate and compare the methods